Short-Term Postoperative Depression and Anxiety in Patients with Differentiated Thyroid Carcinoma: Assessment of Potential Oncologic-Psycho Relevance - Lin Chen; Ningning Ren; Qing Yang; Xingsong Tian (International Journal of Endocrinology)
Objective: To understand whether TSH suppressive therapy affect short-term postoperative cancer-related depression and anxiety among DTC patients. To evaluate short-term postoperative psychological problems and its relationship with baseline parameters, fatigue, sleep quality, illness perception, and patients’ quality of life. Study Design and Methods: This was a prospective, observational, single center study. This study involved 831 TC patients who consecutively admitted to the inpatient department of hospital between 1st June 2020 and 31th February 2021. Results: Mean scores of the self-rated anxiety scale (SAS) (49.04 vs. 40.69) and self-rated depression scale (SDS) (44.61 vs. 39.86), as well as the incidence of anxiety (41.5% vs. 22.1%) and depression (22.5% vs. 2.4%) significantly decreased 3 months after surgery. For personal and clinical characteristics, low educational background (SAS, β = 1.392; SDS, β = 1.622; and p<0.05), without children (SAS, β = 4.068; SDS, β = 1.873, and p<0.01), FNAC (SAS, β = −0.981; SDS, β = −2.583; and p<0.05), and multifocal tumor (SAS, β = −1.287; SDS, β = −2.681; and p<0.05) were the main effects for both short-term postoperative anxiety and depression. Multiple linear regression analysis identified the serum TSH level as a significant variable associated with worse SAS (Beta = −0.695 and p=0.043) and SDS (Beta = −3.133 and p<0.001) scores 3 months after surgery. FT4 was independently associated with SAS scores (Beta = −0.202 and p<0.001). Patients with middle ATA risk had a significantly higher level of SDS scores (p=0.033). Conclusion: We confirmed that cancer-related anxiety and depression among DTC patients significantly alleviated 3 months after surgery. TSH suppression therapy has profound effects on cancer-related anxiety and depression, and the degree of anxiety and depression significantly deteriorated with the decrease of TSH level.